O benefício de prestação continuada para a pessoa com deficiência (BPC): a importância do BPC para as famílias dos beneficiários residentes nas comunidades ribeirinhas do município de Abaetetuba – PA - SANTOS, Leidiane Ferreira dos (2023)
The objective of this study is to analyze the contribution of the Continuous Benefit Benefit (BPC) to the improvement of the living conditions of the families of beneficiaries assisted / accompanied at CRAS Ribeirinho Pólo 04 in the municipality of Abaetetuba-Pá, the city is located in the region of Baixo Tocantins. The social assistance policy has its historical trajectory marked by several advances and setbacks, which reflect the structural changes of capitalist society, its institutionalization in Brazil was given by legal mechanisms, among them, the Single System of Social Assistance (SUAS) in 2005, which has organized social protection levels, such as basic social protection, which is the responsibility of the Social Assistance Reference Center (CRAS), which provides social assistance services and benefits. The research approach was qualitative, and for the understanding of this work, bibliographical surveys, documentary researches and field research were done, and for the latter, we used a semi-structured interview, applied with 03 family members of the beneficiaries in the localities Rio Costa Sirituba and Rio Urubueua Cabeceira, to maintain confidentiality, families were identified with fictional regional names such as the Açaí, Farinha and Peixe family. The reality of the riverside life makes it difficult for the users and their families to access their social policies, being dependent on the tidal dynamics characteristic of the Amazonian factor, so it is necessary to take into account the specificities and singularity of the region for the planning of the social assistance policy. It was verified that the income obtained through the BPC of the disabled person (PCB / PCD) contributes to the subsistence of the 03 families of the beneficiaries, even though the research shows that it still does not promote the autonomy of its beneficiaries and their relatives. Thus, BPC / PCD provides an income that minimally improves the living conditions of beneficiaries, but this situation does not extend to families, denying social rights that are necessary for the citizenship condition of the subjects. The BPC / PCD is a non-contributory benefit, and aims at the autonomy of the beneficiaries, it occurs that the neoliberal model impute requirements for the granting of these rights, such as per capita income, that makes this autonomy unfeasible. This contradiction generates more social inequalities and the need to rethink social policy, since it is constantly under construction and changes.